2008
DOI: 10.1364/josaa.26.000135
|View full text |Cite
|
Sign up to set email alerts
|

Bragg diffraction of multilayer volume holographic gratings under ultrashort laser pulse readout

Abstract: The multilayer coupled wave theory is extended to systematically investigate the diffraction properties of multilayer volume holographic gratings (MVHGs) under ultrashort laser pulse readout. Solutions for the diffracted and transmitted intensities, diffraction efficiency, and the grating bandwidth are obtained in transmission MVHGs. It is shown that the diffraction characteristics depend not only on the input pulse duration but also on the number and thickness of grating layers and the gaps between holographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The definition of the total diffraction of the system of MRVHG read by a ultrashort pulse is given in Eq. (12). Fig.6 shows the total diffraction efficiency variations with the input pulse duration τ for a two-layer system at 1…”
Section: Total Diffraction Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…The definition of the total diffraction of the system of MRVHG read by a ultrashort pulse is given in Eq. (12). Fig.6 shows the total diffraction efficiency variations with the input pulse duration τ for a two-layer system at 1…”
Section: Total Diffraction Efficiencymentioning
confidence: 99%
“…We denoted it as multi-layer coupled wave theory. Many studies of multilayer VHG have been reported in these years [10][11][12], where a light source is assumed to be continuous wave. Because of its abundant spectrum and high bandwidth, the diffraction properties of MRVHG under illumination by ultrashort pulsed beam (UPB) will be different from that of the monochromatic continuous wave.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, diffraction phenomena in optical communications have a key role in communication network system. Advantages of diffraction devices and gratings make them good candidates for applications in many cases in optical communications including, complex filtering, pulse shaping, processing and precise chromatic dispersion compensation [26][27][28]. So, the study of effects of the temporal coherence on diffraction phenomena is unavoidable in optical communications.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown in [5] that the characteristics of angular selectivity of the structures under study have a series of local maxima, the width of which is determined by the sum width of the whole system (including the intermediate layers), and the envelope of the maxima coincides with the selectivity contour of a single array. In [6], similar structures are called MVHG (Multilayer Volume Holographic Grating) and their diffraction properties are considered as applied to propagation of ultrashort (~50 fs) light pulses. It is shown that the spectral distribution of diffracted light substantially depends on MVHG parameters.…”
Section: Introductionmentioning
confidence: 99%